The effects of ANC follow up on essential newborn care practices in east Africa: a systematic review and meta-analysis - Erkihun Tadesse Amsalu (Nature Portfolio, 2021)
Abstract In the situation of high maternal morbidity and mortality in Sub-Saharan Africa, less than 80% of pregnant women receive antenatal care services. To date, the overall effect of antenatal care (ANC) follow up on essential newborn practice have not been estimated in East Africa. Therefore, this study aims to identify the effect of ANC follow up on essential newborn care practice in East Africa. We reported this review according to the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA). We searched articles using PubMed, Cochrane library, African journal online (AJOL), and HINARI electronic databases as well as Google/Google scholar search engines. Heterogeneity and publication bias between studies were assessed using I2 test statistics and Egger’s significance test. Forest plots were used to present the findings. In this review, 27 studies containing 34,440 study participants were included. The pooled estimate of essential newborn care practice was 38% (95% CI 30.10–45.89) in the study area. Women who had one or more antenatal care follow up were about 3.71 times more likely practiced essential newborn care compared to women who had no ANC follow up [OR 3.71, 95% CI 2.35, 5.88]. Similarly, women who had four or more ANC follow up were 2.11 times more likely practiced essential newborn care compared to women who had less than four ANC follow up (OR 2.11, 95% CI 1.33, 3.35). Our study showed that the practice of ENBC was low in East Africa. Accordingly, those women who had more antenatal follow up were more likely practiced Essential newborn care. Thus, to improve the practice of essential newborn care more emphasis should be given on increasing antenatal care follow up of pregnant women in East Africa.